EDP and the Auditor of the 1970's. - Wagner, John W. (The Accounting Review, 1969)
Abstract In a profession as dynamic as auditing has become, it is certainly not too soon to begin speculating on the challenges EDP will present to the auditor of the 1970's. During the 1960's have witnessed rapid technological advances in EDP, and there appears to be little doubt that the pace will accelerate. Accordingly, the purpose of this article is to indicate where the auditor currently stands in relation to EDP, and the extent to which this relationship is likely to change in the 1970's. Auditing around the computer remains the rule rather than the exception, and auditing through the computer is seldom a requirement that cannot be avoided. In fact, the profession has the situation so well in hand, one cannot help wondering how we achieved this surprising result in view of the expectations to the contrary. Even assuming the 1970's produce a rapid implementation of sophisticated information systems, there are internal and external factors that will help the auditor meet the challenge. Externally, other responsible groups have much the same problems as auditors have. For instance, no matter how the systems of the future as designed, management will still have to maintain adequate control over them. Designers of systems may convert the information and audit trails exclusively to electronic form, but regardless of theft form, the trails must remain for control purposes.